2011
DOI: 10.1186/1750-1164-5-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mandibular reconstruction using an axially vascularized tissue-engineered construct

Abstract: BackgroundCurrent reconstructive techniques for continuity defects of the mandible include the use of free flaps, bone grafts, and alloplastic materials. New methods of regenerative medicine designed to restore tissues depend mainly on the so-called extrinsic neovascularization, where the neovascular bed originates from the periphery of the construct. This method is not applicable for large defects in irradiated fields.MethodsWe are introducing a new animal model for mandibular reconstruction using intrinsic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…These concepts may be useful for reconstruction of complex defects, but the problem of donor site morbidity remains to be solved. Recently, a pilot study using an AV‐loop model in the goat was described to further assess bone regeneration in the mandibular region (Eweida et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These concepts may be useful for reconstruction of complex defects, but the problem of donor site morbidity remains to be solved. Recently, a pilot study using an AV‐loop model in the goat was described to further assess bone regeneration in the mandibular region (Eweida et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…By scaling up the AVL model, clinically approved, mechanically stable bone grafts with a significant volume were prefabricated in sheep or goat models, implying the feasibility of clinical translation in future work (Beier et al, 2011, Beier et al, 2010, Boos et al, 2013). Using the AVL strategy, Eweida et al improved the commonly used ectopic prefabrication approach to the in situ prefabrication approach and tested its clinical translation possibility in goats (Eweida et al, 2011, Eweida et al, 2012, Eweida et al, 2014). The results showed that the AVL strategy induced better vascularization at the central regions and permitted more efficient bone regeneration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A natural solution to this problem is adding a vascular network to the construct before implantation, therefore accelerating its perfusion. Pre-vascularized engineered tissues can be quickly perfused with blood by inosculation with the host vasculature (Laschke et al, 2009) or by surgical anastomosis of feeding and draining blood vessels (Beier et al, 2009;Eweida et al, 2011). Such vascular networks must be highly branched in such a way that no cell is further than 200 μm from a vessel as this is broadly considered as the diffusion limit for oxygen and nutrients in tissues (Jain et al, 2005).…”
Section: Vascularization Strategies In Regenerative Medicinementioning
confidence: 99%